The relationship between abusive supervision and organizational trust: The role of subordinates’ self-esteem - Velez, Maria João (2020)
Interest in abusive supervision (Tepper, 2000) has increased due to its serious personal andorganizational costs. As such, there is a need for additional studies that identify the individuals’ factorsthat can minimize the adverse effects of abusive supervision.Specifically, we predict employee self-esteem as a buffer of the relationship between abusivesupervision, organizational trust and in-role behaviors. Additionally, we suggest organizational trustas a possible mechanism linking abusive supervision to in-role behaviors. Our model was exploredamong a sample of 201 supervisor-subordinate dyads from different organizational settings. The resultsof the moderated mediation analysis supported our hypotheses. That is, abusive supervision wassignificantly related to in-role behaviors via organizational trust when employees’ self-esteem waslow, but not when it was high. These findings suggest that self-esteem buffers the impact of abusivesupervision perceptions on organizational trust, with consequences for performance.